Protective factors of prenatal depression, anxiety and stress: a network analysis of Bernstein’s strengths model - Vasvári, Sarolta; Miklósi, Mónika (Frontiers in Psychiatry, 2025)
ObjectiveSymptoms of depression, anxiety, and stress are highly prevalent during pregnancy and have long-lasting negative effects on the mother and the child. Identifying the complex interrelations of protective factors in a theory-driven way is crucial for designing effective psychosocial interventions. The present study aims to explore the effect of personal strengths, and social and environmental factors on depression, anxiety and stress in a sample of pregnant women using a network model.MethodA sample of 346 pregnant women (gestation age range: 12–40 weeks) completed an online questionnaire, which included the Depression Anxiety Stress Scale (DASS), the World Health Organization Quality of Life Assessment, 26-item version (WHOQOL-BREF), the Multidimensional Scale of Perceived Social Support (MSPSS), the Relationship Assessment Scale (RAS), and the Bernstein’s Strengths Scale (BSS).ResultsThe nodes representing DASS subscales were highly and positively interconnected. Depression demonstrated negative associations with relationship satisfaction, social support, physical and environmental health, emotional balance and self-confidence. Anxiety had negative connections with physical and environmental health and resilience; however, it showed positive relationships with imagination and self-assertion. Stress was significantly and negatively related to physical health, emotional balance, resilience and gratitude. Depression, wisdom, and identity had the highest strength centrality, followed by emotional balance and resilience, indicating that these are the most influential nodes in the network.ConclusionThe findings of this study indicate that multifactorial interventions targeting social, physical, environmental factors, and personal strengths, particularly resilience, emotional balance, and self-confidence, hold potential as effective strategies to enhance maternal mental health during pregnancy.